2015
DOI: 10.1007/s11356-015-5353-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal mineralization behavior of PFOA, PFHxA, and PFOS during reactivation of granular activated carbon (GAC) in nitrogen atmosphere

Abstract: Waste disposal site is one of the important sinks of chemicals. A significant amount of perfluoroalkyl and polyfluoroalkyl substances (PFASs) such as perfluorooctanoic acid (PFOA), perfluorooctane sulfonate (PFOS), and perfluorohexanoic acid (PFHxA) have been brought into it. Because of their aqueous solubility, PFASs are released to landfill effluent waters, from which PFASs are efficiently collected by adsorption technique using granular activated carbon (GAC). The exhausted GAC is reactivated by heating pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 17 publications
2
96
0
Order By: Relevance
“…Incineration of spent GAC would have to be conducted at temperatures that are sufficiently high to mineralize PFASs. During thermal reactivation, PFASs may not be completely mineralized at temperatures used to reactivate GAC (Watanabe et al , ). While the thermal reactivation process oxidizes adsorbed background organic matter and thus effectively restores the adsorption capacity of GAC, the fate of PFASs during thermal reactivation and subsequent use of reactivated GAC require further study (Stroo et al ).…”
Section: Effectiveness Of Drinking Water Treatment Processes For the mentioning
confidence: 99%
“…Incineration of spent GAC would have to be conducted at temperatures that are sufficiently high to mineralize PFASs. During thermal reactivation, PFASs may not be completely mineralized at temperatures used to reactivate GAC (Watanabe et al , ). While the thermal reactivation process oxidizes adsorbed background organic matter and thus effectively restores the adsorption capacity of GAC, the fate of PFASs during thermal reactivation and subsequent use of reactivated GAC require further study (Stroo et al ).…”
Section: Effectiveness Of Drinking Water Treatment Processes For the mentioning
confidence: 99%
“…At 700 °C, that study indicated that a much greater degree of PFAS destruction occurred for PFAS that were adsorbed onto GAC, relative to PFAS in the absence of GAC. However, Watanabe et al ( 2018 ) also showed that a temperature of 1000 °C was necessary for nearly complete destruction of vapor‐phase PFAS constituents. This conclusion was based on mass balance data for PFAS destruction, showing that volatile organic fluorine was <0.1% of adsorbed PFAS when the process was operating at 1000 °C.…”
Section: Ex Situ Remediation Technologiesmentioning
confidence: 99%
“…Multiple studies on thermal destruction of a specific list of PFAS were conducted using solid phases, such as pure PFOS or PFOA as a crystalline powder (Yamada and Taylor ; Krusic and Roe ; Krusic et al ), polyester/cellulose fabric (Yamada et al ), fluorotelomer‐based polymers (Taylor et al ), solid polytetrafluoroethylene polymer pellets (Aleksandrov et al ), or during the reactivation of GAC (Watanabe et al ; Watanabe et al. ). These studies used a thermal gravimetric analysis (TGA) to determine the temperature at which the solid phase PFAS (or the PFAS adsorbed to a solid phase) was gasified into a vapor to facilitate the hypothesized destructive mechanism.…”
Section: Considerations For Available Pfas‐relevant Destruction Technmentioning
confidence: 99%
“…As consideration of the life cycle of PFAS continues to evolve, more recent studies assessing thermal treatment includes a broad list of PFAAs and associated fluoro‐organic compounds as potential by‐products of thermal destruction (Watanabe et al ; Watanabe et al ; Aleksandrov et al ). As a result, the application of commercial incineration to mineralize PFAS in concentrated or dilute aqueous waste streams has become an area of focus for the research community, and was the subject of a recent solicitation for research and development (R&D) proposals from the Strategic Environmental Research and Development Program (SERDP ).…”
Section: Considerations For Available Pfas‐relevant Destruction Technmentioning
confidence: 99%